Web-Based Tourism-Package Sales Information System Using Rapid Application Development Method At PO. Amura Tours - Daniel Alfa Puryono; Fransischa Monica Sari; Moh Rofi (LPPM Poltek ST Paul, 2022)
The booming tourism industry is a huge opportunity to generate profits. Today’s developing technology requires companies to develop online-based information systems. Online-based information system is easy to use and can respond to information needs quickly and precisely so that you can access it from anywhere for the latest information more quickly. One of the tour service businesses that prioritizes these services is Amura Tours, which is a tour service business that provides various kinds of tour packages that require the right information technology assistance. However, the tour package sales system at Amura Tours still uses the old method where visitors are required to come directly to Amura Tours to be able to buy tour packages. This is considered quite inconvenient and less effective because sometimes visitors do not get enough information regarding Amura Tours opening hours. In this study, a tour package sales information system was developed that not only provides information about Amura Tours but also serves online tour package bookings. By using the RAD method, system development becomes faster and more precise in providing information needed for selling tour packages. The system built was tested using the Black Box Testing method, the tested features were able to operate properly and in accordance with the requirements of the needs analysis.